Prispevki Petra pl. Radicsa (1836-1912) o obdobju reformacije na Kranjskem - Žigon, Tanja (Stati inu obstati, 2020)
Publicist, editor, historian and ardent researcher of the Carniolan history Peter von Radics (1836-1912) was one of the most prolific authors of his time. His bibliography contains more than 550 titles, 76 of which are lengthy discussions published in books. In his texts, Radics examined historical, cultural-historical, ethnographic, genealogical and theatrical topics. He was also interested in economic and social issues, and in some papers, he focused on researching the Reformation and Counter-Reformation period in Carniola. The texts and discussions that Radics dedicated to this period can be divided into three sections. On the basis of collected and reviewed archival material, he published a few fragments from the history of Reformation and Counter-Reformation in Carniola, shed light on the role of women in the Reformation and Counter-Reformation period, and reconstructed the lives of selected protagonists in short biographical sketches. He was strongly committed to the noble family of Auerspergs (Turjaški), who - Count Anton Alexander von Auersperg (1806-1876) in particular - financially supported his research and often helped him out of financial difficulties. This is one of the reasons why one of his monographs, dedicated to Herbard VIII von Auersperg (published in 1862), had long been considered a fundamental work and the most comprehensive biography of this Carniolan hero in the fight against the Turks and an ardent advocate of Protestantism. Radics also reprinted and briefly commented on the funeral sermon of Krištof Spindler (1546-1591) at Herbard's funeral in September 1575. Radics' contributions on the Reformation and Counter-Reformation period are based on archival sources and testify to the author's professional and scientific competencies. The article lists such publications and briefly presents their content.
Keywords: Auersperg family; Herbard VIII. Turjaški; history of Counter-Reformation; history of Reformation; Radics, Peter; rodbina Auersperg; zgodovina protireformacije; zgodovina reformacije